Inclusion of Bivalve in Carp Polyculture Ponds Managed by Small Indigenous People Under Barind Tract (Journal of Bio-Science, 2021)
The present experiment was carried out in the household ponds (0.04 to 0.08 ha in area with 1.3 to 2.4 m in depth) of small indigenous people at Barind Tract region, northwest Bangladesh during September, 2017 to June, 2018 to know the growth performance of bivalve with carp. Two different treatments with 3 replicates were used, in treatment one (T1) only the carp polyculture was performed and in treatment two (T2) carp and bivalve polyculture was performed. Good quality of carp fingerlings (Labeo rohita, Gibelion catla, Cirrhinus cirrhousus, Hypophthalmichthys molitrix and Ctenopharyngodon idella) and freshwater bivalve (Lamellidens marginalis) seeds were stocked in the ponds. Stocking density and size of the seeds were similar for all of the study ponds. During the experiment there were no significant differences was observed in growth performance of the fishes between the two different treatments (p